Modelo para la Curación de las Úlceras por Presión Tratadas con Estimulación Eléctrica - Folgueras, J.; Suen, J. E. (Revista Mexicana de Ingenieria Biomedica, 2018)
Pressure ulcers, also known as bed-sores, commonly occur in patients subjected to extended periods of immobility and represent a potentially life-threatening hazard to the patient. The method used by authors to treat these pressure ulcers involves the use of electric stimuli. The authors have developed a simple model that describes the behavior of the superficial layer of small ulcers as a function of time under electric stimulation. The model predicts, with an error no greater than 15%, the total healing time of the ulcer, in the absence of secondary complications, highlighting its value as a prognostic tool.